The feast of All Saints - Rice, Anne, 1941- (New York : Simon and Schuster, 1979)
In the days before the Civil War, there lived a Louisiana people unique in Southern histroy. Though descended from African slaves, they were also descended from the French and Spanish who enslaved them. Called the Free People of Color, this dazzling historical novel chronicles the lives of four of them--men and women caught perilously between the worlds of master and slave, privilege and oppression, passion and pain.
Keywords: Fiction. -- New Orleans (La.)